Transforming growth factor-β in tissue fibrosis - Frangogiannis, Nikolaos (The Journal of experimental medicine, 2020)
TGF-β is extensively implicated in the pathogenesis of fibrosis. In fibrotic lesions, spatially restricted generation of bioactive TGF-β from latent stores requires the cooperation of proteases, integrins, and specialized extracellular matrix molecules. Although fibroblasts are major targets of TGF-β, some fibrogenic actions may reflect activation of other cell types, including macrophages, epithelial cells, and vascular cells. TGF-β-driven fibrosis is mediated through Smad-dependent or non-Smad pathways and is modulated by coreceptors and by interacting networks. This review discusses the role of TGF-β in fibrosis, highlighting mechanisms of TGF-β activation and signaling, the cellular targets of TGF-β actions, and the challenges of therapeutic translation.TGF-β is extensively implicated in the pathogenesis of fibrosis. In fibrotic lesions, spatially restricted generation of bioactive TGF-β from latent stores requires the cooperation of proteases, integrins, and specialized extracellular matrix molecules. Although fibroblasts are major targets of TGF-β, some fibrogenic actions may reflect activation of other cell types, including macrophages, epithelial cells, and vascular cells. TGF-β-driven fibrosis is mediated through Smad-dependent or non-Smad pathways and is modulated by coreceptors and by interacting networks. This review discusses the role of TGF-β in fibrosis, highlighting mechanisms of TGF-β activation and signaling, the cellular targets of TGF-β actions, and the challenges of therapeutic translation.